Integrated Sediment Yield Assessment for Hirehalla Watershed in Koppal District, Karnataka, India Using Remote Sensing and GIS Techniques - Trivedi, Akash (Integrated Journal for Research in Arts and Humanities, 2023)
One measure of geomorphic activity is sediment yield, which is defined as the amount of sediment per unit area removed from a watershed by flowing water during a specified period of time. Changes in sediment yield can signal changes in many elements of the ecosystem, including rates of weathering and erosion, climate and human activity. In present research scenario application of Remote Sensing (RS) and Geographic Information System (GIS) has useful advantages for soil erosion rate assessment with proper management planning, particularly for the remote area (Sharma et al., 2001)[1]. In this study we have recorded all the necessary parameters for 26 mini watersheds of third-order streams to measure soil erosion rate in terms of sediment yield. This research work has been carried out with application of combine model of Universal Soil Loss Estimation (USLE) (Musgrave, 1947)[2] and Catchment Wise Erosion Estimation (CWEE) (Garde et al., 1985)[3] integrated with RS-GIS techniques. A sedimentation yield distribution map has been prepared. There we have considered three classes to depict erosion rate zones like High (190.56-257.8kg/ha/y), Medium (123.3-190.56kg/ha/y), Low 56.1- 123.3kg/ha/y). There highest erosion rate is at 4D3A8D2, E2, G1, I1, K1and K2 sample basins accounting 30.2%. It indicates that the high risk of soil erosion found in the Hirehalla basin. Maximum portion (69.2%) of the Hirehalla watershed falls under the medium and low rate of soil erosion zone.